Pengaruh Penghargaan, Hukuman, dan Lingkungan Kerja terhadap Kinerja Kerja: Studi pada UD Anugrah, Brangkal Sooko Mojokerto - Lingstyana Anggela Octavia; Nersiwad Nersiwad; Kasnowo Kasnowo (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to determine the effect of rewards, punishments, and the work environment on employee performance at UD Anugrah, a company engaged in the small and medium enterprise (SME) sector located in Brangkal, Sooko, Mojokerto. This study uses a quantitative approach with a survey method through a closed questionnaire, which was distributed to 30 permanent employees who have worked for a minimum of five years. This criterion was chosen to ensure that respondents have sufficient work experience to understand the organizational culture and managerial policies implemented in the company. The data analysis technique used was Partial Least Square–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software, which allows for a comprehensive analysis of latent relationships between variables even with a small sample size. The results show that rewards and punishments have a significant positive effect on employee performance, meaning that the more appropriate and consistent the rewards and punishments given, the higher the employee performance. The rewards in question can be financial or non-financial incentives such as recognition and promotion, while punishments are more corrective to work discipline violations. On the other hand, work environment variables were found to have no significant effect, although descriptively several respondents mentioned the importance of comfort and job security. These findings emphasize that HR management in the SME sector needs to pay special attention to reward systems and work discipline as key factors in increasing productivity. This research is expected to serve as a strategic reference for SMEs in designing more effective, efficient employee management policies oriented toward long-term performance improvement. Furthermore, it is crucial for management to regularly evaluate the effectiveness of the systems in place and the penalties applied.